Rejuvenating the [1, 2, 3]-triazolo [1,5-a]quinoxalin-4(5H)-one scaffold: Synthesis and derivatization in a sustainable guise and preliminary antimicrobial evaluation - Pelliccia, Sveva; Alfano, Antonella Ilenia; Gomes Da Assunção, Beatriz Ramos; Turco, Luigia; Lembo, Francesca; Summa, Vincenzo; Buommino, Elisabetta; Brindisi, Margherita (Frontiers in Chemistry, 2023)
The [1,2,3]-triazolo [1,5-a] quinoxalin-4(5H)-one scaffold and its analogues triazole-fused heterocyclic compounds are relevant structural templates in both natural and synthetic biologically active compounds. However, their medicinal chemistry applications are often limited due to the lack of synthetic protocols combining straightforward generation of the central core while also allowing extensive decoration activity for drug discovery purposes. Herein, we report a ‘refreshed’ synthesis of the [1,2,3]-triazolo[1,5-a]quinoxalin-4(5H)-one core, encompassing the use of eco-compatible catalysts and reaction conditions. We have also performed a sustainable and extensive derivatization campaign at both the endocyclic amide nitrogen and the ester functionality, comprehensively exploring the reaction scope and overcoming some of the previously reported difficulties in introducing functional groups on this structural template. Finally, we unveiled a preliminary biological investigation for the newly generated chemical entities. Our assessment of the compounds on different bacterial species (two S. aureus strains, three P. aeruginosa strains, K. pneumonia), and two fungal C. albicans strains, as well as the evaluation of their activity on S. epidermidis biofilm formation, foster further optimization for the retrieved hit compounds 9, 14, and 20.